Sayyid Ahmad Khan Dan Pendidikan Modern: (Studi Historis Transformatif Tentang Pembaharuan Pendidikan Modern Di Anak Benua India) - Djamaiyah Muszandra (Program Studi Pendidikan Islam Anak Usia Dini, 2021)
Abstract:. Human are creatures who need education, both physically dan spiritually. This comprehensive education cannot be separated from the origin of human events, namely recognition of God. This is part of human morality towards its creator. The process of moral education begins with understanding knowledge. Then the practice of knowledge anda accompanied by tawajuh (remember) to God. These three components are one part towards the perfection of human morality.